DIMENSI AKUNTABILITAS PADA KELOMPOK PINA JARING (Indonesian Journal of Social Sciences and Humanities, 2020)
The Accountability dimension in the “Pina Jaring” group aims to regulate financing related to the procurement of raw materials used in the "Pina Jaring" activity and also in solving problems faced by the "Pina Jaring" group. The method used is in-depth interviews. The financial reporting system realized in the “Pina Jaring” group is very simple both in terms of cash receipts and disbursements for operational activities in making nets, so that this management is only based on the trust that is given on an ongoing basis. The financial reporting system has not followed the set standards and managers still do not have the desired qualifications. Currently all members of the "Pina Jaring" group consider that the management accountability of the finances of the management is very important, so that the management can show transparency and accountability of their performance in financial management. In addition, the "Pina Jaring" group is also an organization with a kinship system which only consists of fishermen's wives in Labuhan Bontong Village, if the management takes dirty actions in managing finances, automatically the management has betrayed fellow members of the same profession, namely fellow wives. fishermen who work together to make nets in a “Pina Jaring” group with the aim of increasing their family income